Extending Heritage Tourism beyond Reality with Extended Reality Technologies: A Systematic Literature Review - Abby Lian, Hendrick; Suriati Khartini, Jali; Mohamad Imran, Bandan; Phei Chin, Lim; Yin Chai, Wang; Ally Dian, Hendrick; Nurul Farizah, Ridzuan; Johannes Hamonangan, Siregar; Rufman Iman, Akbar (2025)
This paper is a systematic literature review that outlines the evolution of heritage tourism with the use of extended reality technologies. Through the use of three XR technologies, augmented reality, virtual reality, and mixed reality, travelling becomes a more immersive experience. This review explores the types of extended reality technologies in heritage tourism, what tourists prioritize when using them, and what considerations need to be taken by developers when implementing. The Preferred Reporting Items for Systematic reviews and Meta-Analyses statement was adopted as the methodology. Reports from 2018 to 2025 were gathered from SCOPUS, Web of Science, ScienceDirect, and ProQuest as the source databases. The identification process was according to keywords related to extended reality technologies, heritage, and tourism as a singular domain. 38 reports were deemed eligible after screening for their relevance to the topic, document types, publication status, and written in English. From the conducted analysis, virtual reality was applied more often than augmented reality and mixed, with a steady rise across the years. Tourists prioritized engagement with extended reality technology the most while user collaboration and cognitive-affective factors the least. For the developers, reliability when using extended reality technology was regarded as the biggest concern but information architecture of the system was the least. The findings of this review were limited to English documents for consistency and academic publications according to institutional access. From the analysis, the evolution of heritage tourism relies on humans, the natural environment and technologies as interdependent elements of an ecosystem. The relationship encourages the growth of each involved party socioeconomically and technologically. Future research should investigate applicable methodologies and usability metrics of extended reality technology across diverse forms of heritage.